2002
DOI: 10.1248/bpb.25.235
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Hepatic Cytochrome P450s and Steroidogenic CYP17 by Nonylphenol.

Abstract: Endocrine disrupters are exogenous substances which can influence endocrine function in humans and animals, and a number of these chemicals, termed "xenoestrogens", have estrogenic activity. Artificial xenoestrogens include the alkylphenols, nonylphenol and octylphenol, and bisphenol A. 2,3) Alkylphenol polyethoxylates are widely used as detergents, emulsifiers, and wetting agents in industry. In the environment, nonylphenol occurs predominantly as a degradation product of nonylphenol ethoxylate. 4)Cytochrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Finally, nonylphenol has been shown to reduce the level of CYP1A1 expression in murine Hepa-1c1c7 cells (Jeong et al, 2001) and to inhibit in vitro CYP1A1 activity in rat liver microsomes (Lee et al, 1996) and activities of human cytochrome P450s, including steroidogeneic CYP17 activities (Niwa et al, 2002). Oral administration of nonylphenol decreased hepatic testosterone hydroxylation and CYP2C expression level (Laurenzana et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, nonylphenol has been shown to reduce the level of CYP1A1 expression in murine Hepa-1c1c7 cells (Jeong et al, 2001) and to inhibit in vitro CYP1A1 activity in rat liver microsomes (Lee et al, 1996) and activities of human cytochrome P450s, including steroidogeneic CYP17 activities (Niwa et al, 2002). Oral administration of nonylphenol decreased hepatic testosterone hydroxylation and CYP2C expression level (Laurenzana et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is not known why NP did not act in a dose-dependent fashion, but it is possible that NP is acting as a P450 inhibitor at higher concentrations. NP has been shown to inhibit P450 activity (Lee et al, 1996;Niwa et al, 2002;Acevedo et al, 2005), including testosterone 16β-hydroxylase activity (Acevedo et al, 2005), which has been assigned to the Cyp2b subfamily members. NP is extensively metabolized by rat and human Cyp2b family members (Lee et al, 1998), so NP may be competing with ZOX for Cyp2b-mediated metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…out according to methods described previously. 10) Assay of Progesterone 17α-Hydroxylation Activity Progesterone 17α-hydroxylation activity was determined by methods described previously 8,9) with minor modification. Briefly, the membrane fraction containing CYP17 (120 pmol) and POR (210 pmol) was preincubated at 37°C for 3 min, and the mixture was brought to 500 µL; the incubation mixture consisted of 100 mM potassium phosphate buffer (pH 7.4), 10 mM magnesium acetate, 1 mM NADPH, 1 µM (for inhibition by various steroids) or 5-100 µM (for estimation of inhibition constants [K i values]) progesterone, and 0, 20, 50, or 100 µM steroid hormone.…”
Section: Methodsmentioning
confidence: 99%
“…As summarized in Table 2, 8,9,[13][14][15] it has been reported that the IC 50 value of abiraterone, which also contains a hydroxyl group at C 3 in the A ring and a double bond at C 5 in the B ring, was 0.072 µM.…”
Section: Fig 2 Inhibitory Effect Of 21-hydroxypregnenolone On Humanmentioning
confidence: 97%
See 1 more Smart Citation